Teacher Mindsets Concerning the Malleability of Intelligence and the Appraisal of Achievement in the Context of Feedback - De Kraker-Pauw, Emmy; Van Wesel, Floryt; Krabbendam, Lydia; Van Atteveldt, Nienke (Frontiers in Psychology, 2017)
Abstract The pedagogical beliefs (e.g., beliefs or ‘mindsets’ concerning the malleability of intelligence) that teachers hold may have a far-reaching impact on their teaching behaviour. In general, two basic mindsets can be distinguished with regard to the malleability of intelligence: fixed (entity) and growth (incremental). In this article, we present two studies investigating the associations between teachers’ mindset and 1) their appraisal of students’ achievements and 2) the feedback they provide. Study 1 focuses on the associations between mindset and appraisal. The findings reveal an association between growth mindset and the appraisal of increasing student achievements . Study 2 investigates the impact of teachers’ mindset on the amount and type of oral feedback they provide to their students. Contrarily to expectations, the findings reveal a significant negative correlation between mindset and the amount of feedback. Keywords: teacher beliefs, malleability of intelligence, mindset, appraisal of achievement, feedback